Islamic vs Conventional Market Connectedness under Global Uncertainties: Evidence from GCC Countries - Isti Pujihastuti; Rinda Siaga Pangestuti (AIBPM Publisher, 2026)
Global uncertainty increasingly shapes financial connectedness in oil-dependent economies, particularly in the Gulf Cooperation Council (GCC), where Islamic and conventional markets operate side by side. This study examines the time-varying and directional spillovers between global uncertainty indicators and GCC Islamic and conventional financial indices during 2014–2024. Using the quantitative empirical approach, Dynamic Conditional Correlation GARCH (DCC-GARCH) model and the Diebold-Yilmaz Spillover Index, the analysis evaluates evolving correlations, directional spillovers, and rolling system-wide connectedness. The results show that Islamic and conventional GCC indices remain strongly correlated throughout the sample, while linkages with uncertainty indicators intensify during the 2014–2016 oil price collapse, the COVID-19 pandemic, and the Russia-Ukraine conflict. The rolling Total Connectedness Index (TCI) ranges from 55% to 80%, indicating substantial and crisis-sensitive interdependence. Oil price uncertainty and the GCC conventional index emerge as the main stock transmitters, with the conventional index occupying a central position through strong two-way spillover links. These findings imply that GCC financial stability is highly exposed to external uncertainty, highlighting the need for crisis-responsive risk management and diversification strategies.